2018
DOI: 10.1007/s40617-018-00317-2
|View full text |Cite|
|
Sign up to set email alerts
|

Police Academy Training, Performance, and Learning

Abstract: We conducted empirical analyses of training at 3 large regional police academies in the United States. We objectively examined the performance and learning of 3 classes, a total of 115 cadets, across 3 representative training approaches to defensive and control tactics. Experiment 1 examined the content and effects of single-session or block training across 8 weeks during the academy. Experiment 2 examined the content and effects of spaced sessions with small-group practice and scenario-based feedback across 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Several recent commentaries [ 21 , 22 , 32 , 33 ] highlight the importance of developing representative tasks that promote fidelity between training and operational contexts. In fact, O’Neill et al [ 34 ] caution that if UOF skills are not generalised to on-duty performance, “officers might be more likely to rely on tools such as chemical spray, conducted-energy devices, or firearms” (p. 366). Combined with increased training frequency to deliberately practice essential UOF skills [ 35 ], industry-wide standardisation of police UOF training and evaluation can contribute to improved safety and performance in the field [ 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent commentaries [ 21 , 22 , 32 , 33 ] highlight the importance of developing representative tasks that promote fidelity between training and operational contexts. In fact, O’Neill et al [ 34 ] caution that if UOF skills are not generalised to on-duty performance, “officers might be more likely to rely on tools such as chemical spray, conducted-energy devices, or firearms” (p. 366). Combined with increased training frequency to deliberately practice essential UOF skills [ 35 ], industry-wide standardisation of police UOF training and evaluation can contribute to improved safety and performance in the field [ 4 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared the effectiveness of single session, distributed (i.e., “booster” training), and block training approaches for defensive and control tactics in three recruit academies in the United States. Across protocol types that all consisted fewer than 80 min of training for any given skill, immediate post-training gains were lost over long-term follow-up ( O’Neill et al, 2019 ). All of these protocols were representative of the type and duration of training offered at each police agency, which has to balance instructional needs with operational demands (i.e., number of available officers for training or field duty at any given time).…”
Section: Discussionmentioning
confidence: 99%
“…In general, safety planning involves multiple processes, including a general information gathering, planning potential ways to preventing threats from occurring, and thinking through possible responses if various threatening situations were to occur (Burrese 2019;O'Neill et al 2018;Strong 1996;Vince et al 2014). Significantly more women gun owners in the current study reported strategizing, rehearsing, and scenario planning or asking themselves ''what if'' scenarios to prepare their responses to safety risks than nongun owners.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that having plans for responding to threatening situations may increase feelings of personal control and, thus, reduce anxiety (Löw et al 2015;Moscarello and Le-Doux 2013). It could be that education, training, and practice with a gun are associated with more general attention to safety threats, more safety planning, and increased skills and confidence in facing a threat (Barnhart et al 2018;O'Neill et al 2018;Vince et al 2014). However, it is not clear whether people who have guns for safety view the gun as their only defense or whether they have increased confidence and efficacy with regard to personal safety more widely.…”
Section: Introductionmentioning
confidence: 99%